Microscopic features of vaginal candidiasis and their relation to symptomatology - Sonnex, C. (BMJ Group, 1999)
OBJECTIVES: To document the microscopic features of vaginal candidiasis and to examine the relation between yeast morphology and patient symptomatology. METHOD: The study population comprised women undergoing screening for genital infection at a department of genitourinary medicine. RESULTS/CONCLUSION: Data were collected on 267 women of whom 234 were found to have vaginal candidiasis by vaginal culture. The remaining 33 patients had microscopic features of candidiasis (spores and/or hyphae) but were culture negative. Of the culture positive women, microscopy was positive in 182 (78%). "Spores only" were identified in 65 (28%), "hyphae only" in 16 (7%), and both "spores and hyphae" in 101 (43%). 68% of culture positive women were symptomatic, the commonest symptoms being irritation alone (27%) or irritation plus vaginal discharge (25%). No association was found between yeast morphology (spores, budding/non-budding; hyphae, branching/non-branching) as identified on microscopy of vaginal secretions and symptomatology.